2013
DOI: 10.1007/s10948-013-2193-5
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Postannealing on Structural and Superconducting Properties of Bi-2212 Ceramics

Abstract: The effect of postannealing on the structural and superconducting properties of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…However, the presence of intergrain weak links and the weak flux pinning capability in bulk materials are still drawbacks for reaching high critical current density (J c ) values in these materials [1,2]. As it is well known, the enhancement of J c is one of the most important issues for their practical applications [3][4][5][6][7][8]. As a consequence, many attempts have been performed to increase their current carrying capability.…”
Section: Introductionmentioning
confidence: 99%
“…However, the presence of intergrain weak links and the weak flux pinning capability in bulk materials are still drawbacks for reaching high critical current density (J c ) values in these materials [1,2]. As it is well known, the enhancement of J c is one of the most important issues for their practical applications [3][4][5][6][7][8]. As a consequence, many attempts have been performed to increase their current carrying capability.…”
Section: Introductionmentioning
confidence: 99%
“…Solid-state reaction method is one of the simplest and most harmless methods for preparing of ceramic superconductors involving mixing, calcination and sintering. Also, many works show that high J c values can be easily obtained by optimal adjustments in parameters such as annealing time, post annealing temperature and pelletization pressure [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Other possibility to produce these pinning centers is based on the self-production of isolating phases with the adequate size to act as pinning centers. It has been demonstrated that it is possible to produce this effect on Bi-2212 phase using the phase diagram equilibrium [13,28]. In the case of Bi-2223 superconductor, it is well known that this phase is stable in a range of compositions [29] and temperatures [30] and it can be seen as a good candidate to perform its controlled decomposition to produce pinning centers.…”
Section: Introductionmentioning
confidence: 99%